If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -3 = 2 + 4 Reorder the terms: -3 + 2y = 2 + 4 Combine like terms: 2 + 4 = 6 -3 + 2y = 6 Solving -3 + 2y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2y = 6 + 3 Combine like terms: -3 + 3 = 0 0 + 2y = 6 + 3 2y = 6 + 3 Combine like terms: 6 + 3 = 9 2y = 9 Divide each side by '2'. y = 4.5 Simplifying y = 4.5
| 4x-3=-2x+3 | | 2h-6/4=.5 | | 3a-2a+7+6a=-28 | | 9-4(2t-1)=45 | | ln(60)=x | | 5-2x=-6+8+4x-3 | | 6x+12+3x+6=58.3 | | rtd=rt | | 11-(-6)= | | (4x-7y)-(x-3y)= | | 6x^2+66x+60=0 | | 25+4x^2-4x=3x^2-6x | | -32x^7-8x^6= | | 12x=x-2(16) | | x+.20x=34.80 | | -25+4(2x+5)=-16 | | 2x+3-7x+2=10 | | 3(n+7)=-6 | | X+x+.5x+.5x=360 | | 8t-11=5t-5 | | 15x^2-29x+120=0 | | -4(x+1)=5x+5 | | -4x^2-4x-8=0 | | 15x^2-29x+29=0 | | 4d-13+7=-24 | | 6v+28=2(v+6) | | 4x^2-4v-8=0 | | 0=-16t^2+10t+1 | | [-14+(-7)]+[-8+13]= | | 5x+9=140 | | 3x=2y^2 | | 4d-13=-24 |